Composite coating with good diffusion resistance and oxidation resistance as well as preparation method and application of composite coating

By depositing AlCrTaTiZr high-entropy alloy diffusion barrier and NiAlY coating on the surface of Fe-Cr alloy, the oxidation/carbonization corrosion and elemental interdiffusion problems of Fe-Cr high-temperature alloy in high-temperature environment are solved, and the oxidation resistance of the coating is improved. Service lifespan.

CN119144926APending Publication Date: 2024-12-17BEIHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411294154.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Fe-Cr high-temperature alloys are prone to oxidation/carbonization corrosion in high temperature environments. The interdiffusion of elements between Ni-Al coating and Fe-Cr matrix leads to a reduced oxidation resistance of the coating, and harmful intermetallic compounds precipitate, affecting the matrix performance. .

Method used

AlCrTaTiZr high-entropy alloy diffusion barrier was deposited between Ni-Al coating and Fe-Cr alloy, and dense AlCrTaTiZr high-entropy alloy diffusion barrier layer and NiAlY high-temperature protective coating were prepared through magnetron sputtering technology to inhibit interdiffusion and harmful elements The precipitation of the phase improves the oxidation resistance of the coating.

Benefits of technology

Effectively alleviates the thermal expansion mismatch between the coating and the substrate, enhances adhesion, inhibits elemental interdiffusion and precipitation of harmful phases, extends the service life of Ni-Al coating, and improves the antioxidant properties of the coating. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144926A_ABST
    Figure CN119144926A_ABST
Patent Text Reader

Abstract

The invention discloses a composite coating with good diffusion resistance and oxidation resistance and a preparation method and application of the composite coating. The composite coating is composed of a high-entropy alloy diffusion barrier layer and a high-temperature protective coating. The high-entropy alloy diffusion barrier layer is made of Al Cr T < c > T < d > Zr < e >; the high-temperature protective coating is composed of Ni, Al and Y, and the NiAlY coating is composed of a beta-NiAl phase. According to the composite coating with the good diffusion resistance and oxidation resistance and the preparation method and application of the composite coating, element mutual diffusion between a Fe-Cr high-temperature alloy matrix and the NiAlY coating is effectively restrained through the specific hysteresis diffusion effect of the high-entropy alloy; the consumption of an antioxidant element Al in the NiAlY coating and the precipitation of harmful brittle intermetallic compounds are reduced, and the service life of the composite coating is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coating preparation, and in particular to a composite coating with good diffusion resistance and oxidation resistance, and a preparation method and application thereof. Background Art

[0002] Fe-Cr high temperature alloy has many advantages such as simple composition, low cost, good medium temperature mechanical properties and hot processing plasticity, and has become one of the ideal materials for manufacturing heat exchangers, preheaters and cracking furnaces in the fields of petrochemical, chemical and energy industries. However, coal and other fuels used in industries such as petrochemical, chemical and energy industries are mainly composed of hydrocarbons. The combustion of hydrocarbons will produce products such as CO2, CO2+H2O and CO+H2O+H2. These gas molecules decompose at high temperatures to produce active oxygen atoms and active carbon atoms, which in turn cause serious oxidation / carburization corrosion to iron-based alloy workpieces. Studies have shown that Fe-Cr alloys cannot form a protective chromium oxide layer in harsh environments such as high temperature steam. In a high temperature air environment, even if a continuous chromium oxide layer is formed on the surface of Fe-Cr alloy (Cr≥12%), the iron under the chromium oxide layer is corroded during long-term high temperature exposure, which will affect the formation and stability of chromium oxide and accelerate the corrosion of Fe-Cr alloys. Depositing a layer of aluminide protective coating on the surface of Fe-Cr alloy is considered to be one of the most effective measures to prevent alloy corrosion. Nickel-aluminum intermetallic compounds have become ideal materials for high-temperature corrosion-resistant coatings due to their high melting point, low density, good thermal stability and strong antioxidant properties. When the Ni-Al coating is exposed to a high temperature environment, selective oxidation of Al will occur to form an aluminum oxide protective layer. However, due to the difference in elemental composition, the Ni-Al coating and the Fe-Cr matrix will undergo serious interdiffusion behavior. This not only leads to the formation of a thicker interdiffusion zone between the Ni-Al coating and the Fe-Cr matrix, but also precipitates harmful intermetallic compounds in the interdiffusion zone and the matrix, greatly reducing the antioxidant properties of the Ni-Al coating. Therefore, it is very important to prevent the mutual diffusion of elements between the Ni-Al coating and the Fe-Cr matrix. The most effective method is to add a diffusion barrier between the Ni-Al coating and the Fe-Cr matrix. The types of diffusion barrier materials can be divided into metals and ceramic materials. In recent years, high entropy alloys have entered people's field of vision as diffusion barriers. High entropy alloys are multi-component alloys composed of 5 or more main elements, with the atomic composition of each main element ranging from 5% to 35%. They have the advantages of high entropy effect, hysteresis diffusion effect, strong lattice distortion and excellent thermal stability. Therefore, using high entropy alloys as diffusion barriers has great advantages. The research of Chang et al. showed that a 50nm thick AlCrTaTiZr amorphous high entropy alloy diffusion barrier can inhibit the interdiffusion between Cu and Si at 600℃. However, whether AlCrTaTiZr high entropy alloy can effectively inhibit the interdiffusion of elements between Ni-Al coating and Fe-Cr alloy has not been reported.

[0003] Under high temperature conditions, due to the huge difference in elements, there will be serious mutual diffusion between the high temperature protective coating and the Fe-Cr high temperature alloy substrate, resulting in the consumption of the antioxidant element aluminum in the coating, thereby reducing the protective effect of the coating on the substrate. At the same time, the coating elements diffuse into the substrate and will precipitate harmful brittle intermetallic compounds together with the matrix elements, which will seriously reduce the performance of the substrate.

[0004] Therefore, it is an urgent technical problem to prepare an AlCrTaTiZr high entropy alloy diffusion barrier between the Ni-Al coating and the Fe-Cr alloy to effectively prevent the element interdiffusion behavior between the Fe-Cr alloy and the Ni-Al coating and extend the service life of the Ni-Al coating. Summary of the invention

[0005] The purpose of the present invention is to provide a composite coating with good diffusion resistance and oxidation resistance, and a preparation method and application thereof, wherein a dense AlCrTaTiZr high entropy alloy diffusion barrier is deposited between the high-temperature protective coating and the high-temperature alloy to inhibit the mutual diffusion of elements between the high-temperature protective coating and the substrate and the precipitation of harmful phases, thereby improving the oxidation resistance of the NiAlY coating and extending the service life of the NiAlY coating.

[0006] To achieve the above-mentioned object, the present invention provides a composite coating with good diffusion resistance and oxidation resistance, and a preparation method and application thereof, including a composite coating composed of a high entropy alloy diffusion barrier layer and a high-temperature protective coating;

[0007] The high entropy alloy diffusion barrier is Al a Cr b Ta c Ti d Zr e ;

[0008] The high temperature protective coating is composed of Ni, Al and Y, and the NiAlY coating is composed of β-NiAl phase.

[0009] Preferably, a+b+c+d+e=1, and the range of a, b, c, d and e is 0.05 to 0.35.

[0010] Preferably, the high entropy alloy diffusion barrier layer is an amorphous phase structure with a thickness of 3.8 to 4.2 μm.

[0011] Preferably, the thickness of the high temperature protective coating is 7.4-7.8 μm.

[0012] A method for preparing a composite coating with good diffusion resistance and oxidation resistance comprises the following steps:

[0013] S1. Prepare AlCrTaTiZr high entropy alloy target by vacuum non-consumable arc melting technology;

[0014] S2. Prepare NiAlY alloy target by vacuum non-consumable arc melting technology;

[0015] S3, using magnetron sputtering technology to deposit AlCrTaTiZr high entropy alloy diffusion barrier on the surface of Fe-Cr high temperature alloy substrate;

[0016] S4. Use magnetron sputtering technology to deposit NiAlY high-temperature protective coating on the surface of AlCrTaTiZr high-entropy alloy diffusion barrier.

[0017] Preferably, in step S1, five pure metal raw materials of Al, Cr, Ta, Ti and Zr are weighed, and an AlCrTaTiZr high entropy alloy target is prepared by using vacuum non-consumable arc melting technology.

[0018] Preferably, in step S2, three pure metal raw materials of Ni, Al and Y are weighed, and a NiAlY alloy target is prepared by using a vacuum non-consumable arc melting technology.

[0019] Preferably, in step S3, before depositing the high entropy alloy diffusion barrier, the Fe-Cr substrate is ground and polished with metallographic sandpaper of models 600, 1000, and 2000# and W2.5 diamond polishing paste, respectively. The polished Fe-Cr substrate is ultrasonically cleaned in anhydrous ethanol and deionized water, respectively, and the ultrasonic cleaning time is 15 min. The cleaned Fe-Cr substrate is dried at room temperature, and then the dried Fe-Cr high temperature alloy substrate is mounted on the sample stage of the magnetron sputtering equipment, and the AlCrTaTiZr high entropy alloy target obtained in step S1 is placed on the radio frequency target. The magnetron sputtering parameters are: vacuum degree 9×10 -3 ~1×10 - 4 Pa, the temperature of the Fe-Cr high-temperature alloy substrate is 100-200°C, the power of the AlCrTaTiZr high-entropy alloy target is 250W, and the gas pressure is 0.59-0.61Pa. An AlCrTaTiZr high-entropy alloy diffusion barrier layer deposited on the surface of the Fe-Cr substrate is obtained, and the coating thickness is controlled at 3.8-4.2μm.

[0020] Preferably, in step S4, the AlCrTaTiZr high entropy alloy film sample obtained in step S3 is mounted on a sample stage of a magnetron sputtering device, and the NiAlY alloy target obtained in step S2 is placed on a radio frequency target. The magnetron sputtering parameters are: vacuum degree 9×10 -3 ~1×10 -4Pa, the temperature of the AlCrTaTiZr high entropy alloy thin film sample is 100-200°C, the power of the NiAlY alloy target is 300W, and the gas pressure is 0.69-0.71Pa to obtain an AlCrTaTiZr / NiAlY composite coating, and the thickness of the NiAlY coating is controlled at 7.4-7.8μm.

[0021] The invention discloses a substrate whose surface is covered with a composite coating having good diffusion resistance and oxidation resistance properties.

[0022] Therefore, the present invention adopts the above-mentioned composite coating with good diffusion resistance and oxidation resistance and its preparation method and application, and its technical effects are as follows:

[0023] (1) The thermal expansion coefficient of the AlCrTaTiZr high entropy alloy diffusion barrier provided by the present invention is located between the NiAlY high temperature protective coating and the Fe-Cr substrate, which effectively alleviates the mismatch of the thermal expansion coefficients between the NiAlY coating and the Fe-Cr substrate, enhances the adhesion between the coating and the substrate, and improves the coating quality.

[0024] (2) The AlCrTaTiZr high entropy alloy diffusion barrier provided by the present invention effectively inhibits the element interdiffusion between the NiAlY coating and the Fe-Cr matrix, and also inhibits the precipitation of harmful phases, thereby extending the service life of the Ni-Al coating.

[0025] (3) The present invention utilizes magnetron sputtering technology to prepare composite coatings. By adjusting the sputtering gas pressure and sputtering power, the residual stress in the preparation process is reduced, thereby improving the bonding strength between the substrate and the coating, and between the coatings.

[0026] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 (a) is a small angle X-ray diffraction pattern (GIXRD) of the AlCrTaTiZ high entropy alloy diffusion barrier film in Example 1; Figure 1 (b) is a GIXRD diagram of the AlCrTaTiZr / NiAlY composite coating in Example 1 and the NiAlY coating in Comparative Example 1; Figure 1 (c) is a scanning electron microscope (SEM) cross-sectional morphology image of the AlCrTaTiZr / NiAlY composite coating in this Example 1; Figure 1 (d) is a cross-sectional element line scan of the composite coating in Example 1;

[0028] Figure 2 This is the SEM cross-sectional morphology of the NiAlY coating in Comparative Example 1;

[0029] Figure 3 The oxidation weight gain curves of the Fe-Cr matrix sample, the NiAlY / AlCrTaTiZr composite coating sample and the NiAlY coating sample at 850°C in Example 1 and Comparative Example 1;

[0030] Figure 4 The SEM cross-sectional morphology images of the NiAlY / AlCrTaTiZr composite coating sample and the NiAlY coating sample in Example 1 and Comparative Example 1 after oxidation at 850° C. for 50 hours and 100 hours; Figure 4 (a) is the SEM cross-sectional morphology of the NiAlY coating sample after oxidation at 850°C for 50 hours; Figure 4 (b) is the SEM cross-sectional morphology of the NiAlY coating sample after oxidation at 850°C for 100 hours; Figure 4 (c) is the SEM cross-sectional morphology of the composite coating sample after oxidation at 850°C for 50 hours; Figure 4 (d) is the SEM cross-sectional morphology of the composite coating sample after oxidation at 850°C for 100 hours;

[0031] Figure 5 The present invention is a flow chart of a method for preparing a composite coating with good diffusion resistance and oxidation resistance. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0033] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0034] Embodiment 1

[0035] like Figure 5 As shown, the present invention provides a method for preparing a composite coating with good diffusion resistance and oxidation resistance, and the specific steps are as follows:

[0036] Step 1: Preparation of AlCrTaTiZr high entropy alloy target using vacuum non-consumable arc melting technology

[0037] AlCrTaTiZr high entropy alloy target was prepared by vacuum non-consumable arc melting technology, and Al, Cr, Ta, Ti and Zr single metal particles with a purity of more than 99.97% were used to melt the target. First, based on 2kg ingot, Al, Cr, Ta, Ti and Zr single metal particles were weighed in the ratio of 1:1:1:1:1 in atomic percentage. Then, the weighed metal particles were ultrasonically cleaned in anhydrous ethanol for 10 minutes, dried at room temperature and packaged in a sealed bag for later use. At the same time, the surface of the crucible in the vacuum furnace was wiped clean, and the elements Al, Cr, Ti, Ta and Zr were placed in the crucible in order from low to high melting points. The specific order of discharge was Al, Ti, Zr, Cr and Ta. During smelting, the vacuum was drawn to 4-5×10 - 4 Pa, and filled with high-purity argon gas to 1.0×10 5 Pa was used for protection, and the raw materials were repeatedly smelted 5 times under argon protection to obtain AlCrTiTaZr high entropy alloy ingots. Then the ingots were cut into round high entropy alloy targets with a thickness of 5 mm and a diameter of 101 mm by wire cutting. Finally, the surface oil of the target was removed by metallographic sandpaper, and the high entropy alloy target was placed in anhydrous ethanol for ultrasonic cleaning for 10 to 20 minutes, and then placed in an 80°C oven for drying to obtain AlCrTiTaZr high entropy alloy targets.

[0038] Step 2: Preparation of NiAlY alloy target

[0039] The NiAlY alloy target was prepared by vacuum non-consumable arc melting technology, and the target was melted using Ni, Al and Y single metal particles with a purity of more than 99.97%. Based on a 2kg ingot, the Ni, Al and Y single metal particles were weighed in the ratio of 49.9:49.9:0.2 in atomic percentage. Then, the NiAlY alloy target was obtained by the same experimental method and process as step 2.

[0040] Step 3: Deposit AlCrTaTiZr high entropy alloy diffusion barrier on the surface of Fe-Cr high temperature alloy substrate using magnetron sputtering technology.

[0041] First, the Fe-Cr substrate was ground and polished with 600, 1000, and 2000# metallographic sandpaper and W2.5 diamond polishing paste until the surface showed metallic luster. The polished Fe-Cr substrate was placed in anhydrous ethanol and deionized water for ultrasonic cleaning, and the ultrasonic cleaning time was 15 min. The cleaned Fe-Cr substrate was dried at room temperature. Then, the dried Fe-Cr substrate was placed on the sample stage of magnetron sputtering, and the AlCrTaTiZr high entropy alloy target was placed on the RF target. The cavity was closed, and the mechanical pump was turned on to evacuate to below 8.0 Pa, and then the molecular pump was turned on. When the vacuum was evacuated to 1.0×10 -4 Pa, argon gas is introduced into the vacuum chamber. The high entropy alloy target is pre-sputtered for 5 minutes before formal sputtering to remove impurities and oxides on the target surface. In order to obtain uniform coating thickness and composition, the stage rotates at a speed of 5rpm. The temperature of the Fe-Cr high temperature alloy substrate is 100-200℃, the power of the AlCrTaTiZr high entropy alloy target is 250W, and the gas pressure is 0.6Pa. The AlCrTaTiZr high entropy alloy diffusion barrier deposited on the surface of the Fe-Cr substrate is obtained, and the coating thickness is controlled at 4.0μm.

[0042] Step 4: Use magnetron sputtering technology to deposit NiAlY high temperature protective coating on the surface of AlCrTaTiZr high entropy alloy diffusion barrier. Place the NiAlY alloy target obtained in step 2 on the RF target, and place the AlCrTaTiZr high entropy alloy film sample obtained in step 3 on the sample table. Then, follow the same experimental method and process as step 3 to obtain AlCrTaTiZr / NiAlY composite coating. The parameters of magnetron sputtering are: vacuum degree 1x10 -4 Pa, the temperature of the AlCrTaTiZr high entropy alloy thin film sample is 100-200 °C, the power of the NiAlY alloy target is 300 W, the gas pressure is 0.7 Pa, and the thickness of the NiAlY coating is controlled at 7.6 μm.

[0043] Comparative Example 1

[0044] This comparative example provides a method for preparing a NiAlY high-temperature protective coating, which is different from Example 1 in that the AlCrTaTiZr high-entropy alloy diffusion barrier is not deposited, and the NiAlY coating is directly deposited on the surface of the Fe-Cr high-temperature alloy using magnetron sputtering technology.

[0045] Test Example 1

[0046] The AlCrTaTiZr / NiAlY composite coating in Example 1 was characterized and the results are as follows: Figure 1 shown. Figure 1(a) is the GIXRD pattern of the AlCrTaTiZ high entropy alloy diffusion barrier film. The results show that the AlCrTaTiZr high entropy alloy diffusion barrier is an amorphous structure. Figure 1 (b) shows that the NiAlY outer layer in the composite coating consists only of β-NiAl phase. Figure 1 (c) is the SEM cross-sectional morphology of the AlCrTaTiZr / NiAlY composite coating, and the results show that the thickness of the AlCrTaTiZr diffusion barrier and the NiAlY coating are 4.0μm and 7.6μm, respectively. The coating and the substrate, and the coatings in the composite coating are tightly connected without any obvious structural defects. Figure 1 The EDS line scan results of (d) show that the composition of the high entropy alloy diffusion barrier is: Al 13.01%, Cr 25.78%, Ta24.16%, Ti 17.56% and Zr 19.49%. The composition of the NiAlY coating is: Ni 51.07% and Al 48.93%.

[0047] Test Example 2

[0048] The NiAlY coating in Comparative Example 1 was structurally characterized. Figure 1 (b) is the GIXRD pattern of the NiAlY coating, which is composed only of β-NiAl phase. Figure 2 The SEM cross-sectional morphology of the NiAlY coating shows that the thickness of the NiAlY coating is 7.6 μm. Some micropores appear at the junction of the NiAlY coating and the substrate, and the appearance of micropores reduces the adhesion between the NiAlY coating and the substrate. On the contrary, the composite coating does not have any structural defects, indicating that the addition of the high entropy alloy diffusion barrier improves the coating quality.

[0049] Test Example 3

[0050] The high temperature oxidation resistance of the composite coating and NiAlY coating prepared in Example 1 and Comparative Example 1 was tested. Figure 3 The results show that the oxidation weight gains of NiAlY and composite coatings after oxidation for 100 h at 850 °C are 0.45 and 0.39 mg·cm, respectively. -2 , indicating that the addition of high entropy alloy improves the oxidation resistance of NiAlY coating.

[0051] Test Example 4

[0052] The interdiffusion behaviors of interface elements of the composite coating and the NiAlY coating prepared in Example 1 and Comparative Example 1 were tested. Figure 4(a) and 4(b) are SEM cross-sectional morphology images of NiAlY coating samples after oxidation at 850℃ for 50 hours and 100 hours. The results show that the thickness of the interdiffusion zone formed by NiAlY coating and substrate after oxidation for 50 hours and 100 hours is 13.2μm and 15.9μm respectively, and a large amount of FeAl3 brittle intermetallic compounds are precipitated in the interdiffusion zone and substrate. After oxidation for 100 hours, NiAlY coating has undergone severe internal oxidation. On the contrary, Figure 4 (c) and 4(d) are SEM cross-sectional morphology images of the composite coating samples after oxidation at 850℃ for 50 hours and 100 hours. The thickness of the inter-diffusion zone formed in the composite coating after oxidation for 50 hours and 100 hours is 4.8μm and 7.1μm respectively, and no FeAl3 is precipitated. At the same time, the composite coating only undergoes slight internal oxidation. The above results show that the addition of AlCrTaTiZr diffusion barrier not only inhibits the inter-diffusion of elements between NiAlY coating and substrate and the precipitation of harmful phases, but also improves the oxidation resistance of NiAlY coating and prolongs the service life of NiAlY coating.

[0053] Therefore, the present invention adopts the above-mentioned composite coating with good diffusion resistance and oxidation resistance and its preparation method, which is mature, reliable and has good repeatability.

[0054] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A composite coating with good diffusion resistance and oxidation resistance, characterized in that: The composite coating comprises a high entropy alloy diffusion barrier layer and a high temperature protective coating; The high entropy alloy diffusion barrier is Al a Cr b Ta c Ti d Zr e ; The high temperature protective coating is composed of Ni, Al and Y, and the NiAlY coating is composed of β-NiAl phase.

2. The composite coating with good diffusion resistance and oxidation resistance according to claim 1, characterized in that: a+b+c+d+e=1, and the range of a, b, c, d and e is 0.05 to 0.

35.

3. The composite coating with good diffusion resistance and oxidation resistance according to claim 1, characterized in that: The high entropy alloy diffusion barrier layer is an amorphous phase structure with a thickness of 3.8 to 4.2 μm.

4. The composite coating with good diffusion resistance and oxidation resistance according to claim 1, characterized in that: The thickness of the high temperature protective coating is 7.4-7.8 μm.

5. A method for preparing a composite coating having good diffusion resistance and oxidation resistance, characterized in that: The following steps are involved: S1. Weigh five pure metal raw materials, namely Al, Cr, Ta, Ti and Zr, and prepare AlCrTaTiZr high entropy alloy target by vacuum non-consumable arc melting technology; S2, weighing three pure metal raw materials of Ni, Al and Y, and preparing NiAlY alloy target by vacuum non-consumable arc melting technology; S3, using magnetron sputtering technology to deposit AlCrTaTiZr high entropy alloy diffusion barrier on the surface of Fe-Cr high temperature alloy substrate; S4. Use magnetron sputtering technology to deposit NiAlY high-temperature protective coating on the surface of AlCrTaTiZr high-entropy alloy diffusion barrier.

6. The method for preparing a composite coating having good diffusion resistance and oxidation resistance according to claim 5, characterized in that: In step S3, the Fe-Cr substrate is ground and polished before depositing the high entropy alloy diffusion barrier, the polished Fe-Cr substrate is ultrasonically cleaned in anhydrous ethanol and deionized water respectively, the cleaned Fe-Cr substrate is dried at room temperature, and then the dried Fe-Cr high-temperature alloy substrate is mounted on the sample stage of the magnetron sputtering equipment, and the AlCrTaTiZr high entropy alloy target obtained in step S1 is placed on the radio frequency target to obtain an AlCrTaTiZr high entropy alloy diffusion barrier layer deposited on the surface of the Fe-Cr substrate.

7. The method for preparing a composite coating having good diffusion resistance and oxidation resistance according to claim 5, characterized in that: In step S4, the AlCrTaTiZr high entropy alloy thin film sample obtained in step S3 is mounted on a sample stage of a magnetron sputtering device, and the NiAlY alloy target obtained in step S2 is placed on a radio frequency target to obtain an AlCrTaTiZr / NiAlY composite coating.

8. The method for preparing a composite coating having good diffusion resistance and oxidation resistance according to claim 5, characterized in that: In step S3, the magnetron sputtering parameters are: vacuum degree 9×10 -3 ~1×10 -4 Pa, the temperature of the Fe-Cr high-temperature alloy substrate is 100-200°C, the power of the AlCrTaTiZr high-entropy alloy target is 250W, and the gas pressure is 0.59-0.61Pa.

9. The method for preparing a composite coating having good diffusion resistance and oxidation resistance according to claim 5, characterized in that: In step S4, the magnetron sputtering parameters are: vacuum degree 9×10 -3 ~1×10 -4 Pa, the temperature of the AlCrTaTiZr high entropy alloy thin film sample is 100-200°C, the power of the NiAlY alloy target is 300W, and the gas pressure is 0.69-0.71Pa.

10. A substrate having a surface covered with a composite coating having good diffusion resistance and oxidation resistance as claimed in any one of claims 1 to 4.